1991
DOI: 10.1128/jvi.65.12.6535-6543.1991
|View full text |Cite
|
Sign up to set email alerts
|

trans activation of the simian virus 40 late promoter by large T antigen requires binding sites for the cellular transcription factor TEF-1

Abstract: Simian virus 40 (SV40) T antigen stimulates the level of transcription from several RNA polymerase II promoters, including the SV40 late promoter. The mechanism of trans activation appears to be indirect since binding of T antigen to specific DNA sequences is not required. However, specific promoter elements that respond to T antigen have not previously been defined. We identified DNA sequences from the SV40 late promoter whose ability to stimulate transcription is induced by the expression of T antigen. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…TEF-1 was first identified as a HeLa cell protein that binds cooperatively to tandem repeats of the GT-IIC or Sph enhansons from the simian virus 40 (SV40) enhancer (Davidson et al, 1986(Davidson et al, , 1988Wildeman et al, 1986;Xiao et al, 1987). These TEF-1 binding sites, which have highly degenerate nucleotide sequences, activate transcription from the SV40 early promoter (Davidson et al, 1986;Herr and Clarke, 1986;Zenke et al, 1986;Nomiyama et al, 1987;Ondek et al, 1987Ondek et al, , 1988Schirm et al, 1987;Fromental et al, 1988) and mediate large T antigen activation of the SV40 late promoter (May et al, 1987;Casaz et al, 1991;Gruda and Alwine, 1991;Kelly and Wildeman, 1991). The latter effect possibly involves direct interaction between TEF-l and large T antigen (Gruda et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…TEF-1 was first identified as a HeLa cell protein that binds cooperatively to tandem repeats of the GT-IIC or Sph enhansons from the simian virus 40 (SV40) enhancer (Davidson et al, 1986(Davidson et al, , 1988Wildeman et al, 1986;Xiao et al, 1987). These TEF-1 binding sites, which have highly degenerate nucleotide sequences, activate transcription from the SV40 early promoter (Davidson et al, 1986;Herr and Clarke, 1986;Zenke et al, 1986;Nomiyama et al, 1987;Ondek et al, 1987Ondek et al, , 1988Schirm et al, 1987;Fromental et al, 1988) and mediate large T antigen activation of the SV40 late promoter (May et al, 1987;Casaz et al, 1991;Gruda and Alwine, 1991;Kelly and Wildeman, 1991). The latter effect possibly involves direct interaction between TEF-l and large T antigen (Gruda et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It contains ATPase and helicase activities, binds DNA, directs viral DNA replication, represses transcription from the SV40 early promoter, and binds the tumor suppressor proteins Rb, p53, and p107. Tag is also a promiscuous transactivator of most cellular and viral promoters, including the SV40 late promoter (references 18 and 48 and references cited therein) which can be activated by both TEF-1-dependent (8,32) and TEF-1-independent mechanisms (7). Much of Tag's transactivation of the SV40 late promoter is achieved by inducing replication of the viral genome to a high template copy number, thereby enabling the titration of cellular repressors of this promoter (60).…”
mentioning
confidence: 99%
“…CV-1 cells were maintained in Dulbecco's modified Eagle medium (Hazelton) with 10% (vol/vol) newborn calf serum (Gibco), 50 U of penicillin G per ml, and 50 g of streptomycin (Gibco) per ml. Transfections were performed by the calcium phosphate precipitation method (20), modified as described previously (11). Transfection mixtures generally included 2 g of CAT reporter plasmid DNA; 0 or 2 g of either p6-1, to express wild-type T antigen, or plasmids encoding mutant T antigens; 0.5 g of pXGH5 or pTKGH; and pBluescript SKϩ (Stratagene) to bring the total amount of DNA to 20 g/10-cm-diameter plate.…”
Section: Methodsmentioning
confidence: 99%
“…T antigen activates the late promoter through a replication-independent stimulation of late promoter activity (6,26). Mutagenesis of the late promoter has indicated that binding sites for the cellular transcription factor TEF-1 are necessary for activation by T antigen (11,17,27,28,47). In addition, these sites are sufficient to confer T-antigen inducibility on heterologous promoters (11,21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation